Performance of public health surveillance systems during the influenza A(H1N1) pandemic in the Americas: testing a new method based on Benford's Law (2011)
The A(H1N1) influenza pandemic has been a challenge for public health surveillance systems in all countries. An objective evaluation has not been conducted, as yet, of the performance of those systems during the pandemic. This paper presents an algorithm based on Benford’s Law and the mortality ratio in order to evaluate the quality of the data and the sensitivity of surveillance systems. It analyses records of confirmed cases reported to the Pan American Health Organization by its 35 member countries between epidemiological weeks 13 and 47 in 2009. Seventeen countries did not fulfil Benford’s Law, and mortality exceeded the regional average in 40% of the countries. The results suggest uneven performance by surveillance systems in the different countries, with the most frequent problem being low diagnostic coverage. Benford’s Law proved to be a useful tool for the evaluation of a public health surveillance system’s performance.